2022
DOI: 10.3389/fenvs.2022.913293
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution characteristics and potential ecological risk assessment of soils around three typical antimony mining areas and watersheds in China

Abstract: China is the largest antimony resource globally. The mining and smelting of antimony will inevitably have a significant impact on the surrounding and downstream farmlands of the mining area, Therefore, it is necessary to understand the pollution characteristics of antimony and evaluate its potential environmental risks. In this paper, three typical antimony mining areas were used as research districts to analyze the contents of heavy metals in soils of the mining areas and watersheds. The single-factor polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…This may be ascribed to heavy metals in the soil were absorbed by plants. In previous study ( Qi et al, 2022 ), it was found that the dominant herbaceous plants in native Compositae and Gramineae had strong enrichment and transport ability to heavy metals such as Cd, Cr and Ni. Moreover, the contents of heavy metals in the surface layer of soil were higher than those in 10–20 cm layer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may be ascribed to heavy metals in the soil were absorbed by plants. In previous study ( Qi et al, 2022 ), it was found that the dominant herbaceous plants in native Compositae and Gramineae had strong enrichment and transport ability to heavy metals such as Cd, Cr and Ni. Moreover, the contents of heavy metals in the surface layer of soil were higher than those in 10–20 cm layer.…”
Section: Discussionmentioning
confidence: 93%
“…Among them, the status of soil heavy metals pollution in karst areas in different land and vegetation cover types appeared in karst areas ( Han et al, 2022 ; Liu et al, 2022 ; Sun et al, 2020 ). Such as natural background, agricultural activity area ( Zhang et al, 2021 ; Han et al, 2012 ; Zeng et al, 2019 ), mining area ( Zhou et al, 2022 ; Zhang et al, 2022 ; Wang et al, 2022b ; Qi et al, 2022 ) has become a major thrust of research. The research content is mainly based on the distribution characteristics of soil heavy metal content or how to reduce the heavy metal content in soil.…”
Section: Introductionmentioning
confidence: 99%
“…This method not only considers the influence of concentration and toxicological characteristics of heavy metals in a specific environment, but also eliminates the difference caused by the background value of heavy metals. The calculation formula are as follows (Qi et al, 2022b):…”
Section: Potential Ecological Risk Index (Ri)mentioning
confidence: 99%
“…The potential ecological risk index (RI) was used to evaluate the all-round potential ecological risk due to heavy metal accumulation in soils [8,14,26,31,40,45]. The integrated RI is calculated by the following Formulas (3) and ( 4): Table S3 summarized the classification of i r E and RI grades for heavy metal contamination.…”
Section: Pollution and Risk Assessment Analysismentioning
confidence: 99%